Potassium‐Ion Batteries: Sulfur‐Grafted Hollow Carbon Spheres for Potassium‐Ion Battery Anodes (Adv. Mater. 30/2019). Issue 30 (23rd July 2019) - Ding, Jia; Zhang, Hanlei; Zhou, Hui; Feng, Jun; Zheng, Xuerong; Zhong, Cheng; Paek, Eunsu; Hu, Wenbin; Mitlin, David
Abstract : In article number1900429, Cheng Zhong, David Mitlin, and co‐workers describe covalently bonded sulfur‐grafted hollow carbon nanospheres that are created and utilized in potassium‐ion battery (KIB) anodes with exceptional performance. The baby dinosaurs in the image represent the sulfur species that are ravenous for their preferred meal of potassium ions that roam their Electro‐Jurassic world in large herds. The eggs that these dinosaurs hatched from represent their carbon sphere sulfur hosts.